FACTORS AFFECTING FIRM VALUE ON TRANSPORTATION COMPANIES LISTED ON THE IDX - Nadine Hadisoewono; Agustin Ekadjaja (Graduate Program of Universitas Tarumanagara, 2024)
This research was conducted with the aim of determining the effect of profitability, liquidity, capital structure and company size on the value of companies with the transportation sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. Totals of 75 observational data originated from 25 transportation companies. The technique used in this study is purposive sampling. The hypothesis testing method in this research uses the multiple regression analysis testing was performed using IBM Statistic's SPSS 29 program. This research uses Tobin’s Q as a parameter to measure a firm value. For profitability uses Return on Asset (ROA) as a proxy, liquidity uses Current Ratio (CR) as a proxy, capital structure us Debt on Equity Ratio (DER), and Company Size uses Size as a proxy. Based on the outcome of the processed data, profitability has a significant positive effect on the value of the company, liquidity has a significant negative effect on the value of the company, capital structure has a significant negative effect on the value of the company and company size has a significant negative effect on the value of the company. This research is expected to help potential investor in making decisions to invest or not.